Mitochondrial mutation commonly associated with Leber's hereditary optic neuropathy observed in a patient with Wolfram syndrome (DIDMOAD). Issue 4 (April 1994) - Pilz, D; Quarrell, O W; Jones, E W
Abstract : DIDMOAD is usually considered an autosomal recessive condition, with wide phenotypic variation, but the possibility of mitochondrial mutations occurring in this condition has been considered. A 19 year old man presented with long standing diabetes mellitus, optic atrophy, and grand mal seizures. Further investigations showed unilateral sensorineural hearing loss and the most common mitochondrial DNA mutation associated with Leber's hereditary optic neuropathy, which was inherited from his mother. This suggests the DIDMOAD phenotype is a mitochondrial disorder in some cases and is likely to have a heterogeneous aetiology.